CircPCBP2 promotes the stemness and chemoresistance of DLBCL via targeting miR‐33a/b to disinhibit PD‐L1. Issue 8 (14th June 2022) - Dong, Lihua; Huang, Jingjing; Gao, Xue; Du, Jianwei; Wang, Yesheng; Zhao, Lingdi
Abstract: Diffuse large B‐cell lymphoma (DLBCL) is the most common lymphoid malignancy with a high relapse rate of up to 40%. The prognosis of the disease needs improvement and requires a understanding of its molecular mechanism. We investigated the mechanisms of DLBCL development and its sensitivity to chemotherapy by focusing on circPCBP2/miR‐33a/b/PD‐L1 axis. Human DLBCL specimens and cultured cancer cell lines were used. Features of circPCBP2 were systematically characterized through Sanger sequencing, Actinomycin D, RNase R treatment, and FISH. The expression levels of circPCBP2, miR‐33a/b, PD‐L1, stemness‐related markers, ERK/AKT and JAK2/STAT3 signaling were measured using qRT‐PCR, western blotting, and immunohistochemistry. Stemness of DLBCL cells was assessed through spheroid formation assay and flow cytometry. Cell viability and apoptosis upon cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) treatment were determined using MTT assay and flow cytometry, respectively. Interactions of circPCBP2‐miR‐33a/b and miR‐33a/b‐PD‐L1 were validated using dual luciferase activity assay and RNA‐RIP. Nude mouse xenograft model was used to assess the function of circPCBP2 in DLBCL growth in vivo. circPCBP2 was upregulated in human DLBCL specimens and cultured DLBCL cells while miR‐33a/b was reduced. Knockdown of circPCBP2 or miR‐33a/b overexpression inhibited the stemness of DLBCL cells and promoted cancer cell apoptosis upon CHOP treatment. circPCBP2 directly bound with miR‐33a/b while miR‐33a/b targeted PD‐L1 3'‐UTR. circPCBP2 disinhibited PD‐L1 signaling via sponging miR‐33a/b. miR‐33a/b inhibitor and activating PD‐L1 reversed the effects of circPCBP2 knockdown and miR‐33a/b mimics, respectively. circPBCP2 knockdown restrained DLBCL growth in vivo and potentiated the anti‐tumor effects of CHOP. In conclusion, circPCBP2 enhances DLBCL cell stemness but suppresses its sensitivity to CHOP via sponging miR‐33a/b to disinhibit PD‐L1 expression. circPCBP2/miR‐33a/b/PD‐L1 axis could serve as a diagnosis marker or therapeutic target for DLBCL. Abstract : 1)CircPCBP2 was elevated while miR‐33a/b was reduced in DLBCL specimens and cells. 2)Knockdown of circPCBP2 or miR‐33a/b overexpression suppressed DLBCL cell stemness and enhanced their sensitivity to CHOP.